The effects of video feedback on coaches' behavior and the coach-athlete relationship - Meeus, M.; Simon P.; Serpa, S.; de Cuyper, B. (Journal of Clinical Sport Psychology, 2010)
This study examined the effects of video feedback on the nonverbal behavior of handball coaches, and athletes` and coaches` anxieties and perceptions. One intervention group (49 participants) and one control group (63 participants) completed the Coaching Behavior Assessment System, Coaching Behavior Questionnaire, and Competitive State Anxiety Inventory-2 on two separate occasions, with 7 weeks of elapsed time between each administration. Coaches in the intervention condition received video feedback and a frequency table with a comparison of their personal answers and their team`s answers on the CBAS. Repeated-measures ANOVAs showed that over time, athletes in the intervention group reported significantly less anxiety and perceived their coaches significantly more positively compared with athletes in the nonintervention condition. Over time, coaches in the intervention group perceived themselves significantly more positively than coaches in the nonintervention condition. Compared with field athletes, goalkeepers were significantly more anxious and perceived their coaches less positively. It is concluded that an intervention using video feedback might have positive effects on anxiety and coach perception and that field athletes and goalkeepers possess different profiles.